Forgotten origin - Strong, Steven, 1953-; Strong, Evan (University Press of America, Incorporated, 2011)
"Forgotten Origin is the third in a series of books dedicated to the first Homo sapiens: the Australian Aboriginal people. Steven Strong and Evan Strong continue in their investigation into the global impact of Aboriginal people sailing from, never to, Australia no less than 50,000 years ago, paying particular attention to the shared principles found within many Gnostic scriptures and the Dreaming. As radical as this theory may appear, the rigor applied, whether through mtDNA, Y Chromosomes, skull morphology or historical accounts, and the religious ancestry upon which this hidden history is founded, demands serious consideration"--Page 4 of cover.